THE EFFECTIVENESS OF USING ENGLISH CARTOON FILM IN IMPROVING STUDENTS’ NOUN VOCABULARY MASTERY - Islamiyah, Nurul Fikri; Jumiaty , Andi Asri; Burhanuddin, Wildhan (FKIP Unismuh Makassar, 2023)
The aims of this research was to find out How Effective the use of English Cartoon Film in Improving Students' Vocabulary mastery. This research conducted by used Quantitative method with a Pre-Experimental design with one group of pre-test and post-test. This research population consisted of eighth grade students at SMP Negeri 2 Mappakasunggu, with the research sample being Class VIII C, which consisted of 23 Students, selected by purposive sampling technique. The data from this research gathered through the supply of pre-test and post-test materials to be utilized as a comparison to find out how the improvement of students' vocabulary mastery before and after using English cartoon film with as a teaching/learning media. The results of this research revealed that using English cartoon films as a media of teaching and learning is effective for students in eighth grade students of SMP Negeri 2 Mappakasunggu in improving their vocabulary mastery. This is demonstrated by how much the student's grades have improved. where the pre-test mean score of students is 42.17 and the post-test mean score of students is 70.43, indicating a 67.01% increase in students in this research. Furthermore, data analysis results show that the value of t-test (13.57) is greater than the value of t-table (2.074). Based on these findings, it is possible to conclude that there is a significant difference in students'